The Integration of Islam and Science (An Analysis of the Problematics and Levels of Integration) - Ach. Maimun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Lagging behind in the fields of science and technology is a problem that has emerged since the end of the Middle Ages (18th century AD), so that since then Muslims have been infected with